The emergence of certified organic agriculture in Pakistan: actor dynamics, knowledge production, and cosumer demand - Poerting, Julia (Asien, 2015)
Certified Organic Agriculture (COA) is a much debated alternative to conventional and industrialized farming, with recent scholarship having paid attention to different aspects of organic commodities within a global agrofood system. Organic standards link consumers in the Global North with producers in the Global South, and transport agricultural knowledge around the global. For farmers in the Global South, knowledge therefore plays a central role in their successful conversion to COA. This paper, based on ethnographic fieldwork in Pakistan in 2013 and 2014, focuses on the country’s small but fast-growing organic agricultural sector and examines how the different actors involved in it produce and circulate knowledge about how to cultivate and market organic food crops. Producers, agricultural universities, government departments, private sector actors, and urban farmers all have to exchange knowledge so as to overcome a multitude of challenges. An analysis of the processes of knowledge production and circulation is central to understanding how knowledge travels and which practices take hold, and how.
Gesehen am 16.06.2020
Keywords: Pakistan